PENGUATAN NILAI MODERASI BERAGAMA MELALUI AJARAN AGAMA HINDU - Yunitha Asri Diantary Ni Made (Jnanasiddhanta : Jurnal Teologi Hindu, 2023)
Indonesia is a nation consisting of people with a diversity of cultures, religions, races, languages, ethnicities, traditions and others. The people are close to religious life and every religious activity is protected by the constitution. As the first precept in Pancasila which explains "Belief in the One and Only God" shows that this country practices the principles and values of religion that are recognized in Indonesia. Every adherent of a religion has its own truth values and teachings, behind the plurality that is owned it is necessary to maintain harmony without having to demean other religions, this is a challenge for the government in realizing harmony behind diversity. The concept of moderation is the solution in realizing a nation that is peaceful, full of tolerance and harmony. In this case Hinduism as one of the recognized religions in Indonesia has religious teachings that are relevant to the values of religious moderation. Where is the teaching of tolerance in Hinduism which prioritizes humanity in people's lives, apart from that the concept of ahimsa which emphasizes compassion as a form of implementing non-violence values, as well as the concept of yama brata as a teaching that gives understanding to people to control themselves so they can carry out the principles contained in this nation and the teachings of tattwan asi which lead humanity to the universal family. Hindu religious teachings are able to strengthen the value of religious moderation so it is important to implement it in religious life. Keywords: strengthening the value of religious moderation, Hindu religious teachings.